Output gaps and the government budget balance: The case of Finland - Kaare Guttorm Andersen; Hanna-Leena Männistö (Bank of Finland, 1995)
The purpose of this paper is to find a suitable method for estimating output gaps and calculating the cyclically adjusted government budget balance for Finland.Several different approaches for estimating a reference trend are briefly evaluated and a calculation of the cyclically adjusted government budget balance is presented.We review the production function approach, the middle-expansion trend, the Hodrick-Prescott filter and a multivariate filter developed by Laxton and Tetlow.We conclude that the Hodrick-Prescott filter and the multivariate filter have some properties that make them well suited for routine analysis of discretionary fiscal policy.Income and expenditure elasticities are estimated using BOF4 model simulations and cross checked by simple regression analysis.The cyclically adjusted government budget balance is then calculated for both central and general government using the reference trends and the estimated budget elasticities.Measuring the cyclically adjusted budget balance for the central government has important implications, because surpluses of the large pensions funds have improved the general government budget balance, which has caused a serious misjudgment of the underlying fiscal stance.Our calculations suggest that Finland's present government deficit is more structural than cyclical.
URN:NBN:fi:bof-20140807514
Keywords: 330